Fatores envolvidos na implementação da telessaúde: analisando percepções de profissionais de saúde, pacientes e população - Fernandes, Lívia Gaspar (2021)
Background: Telehealth is based on information and communication means to deliver health services, disseminate health-related information, and as an alternative to continue care. Telehealth advantages include the potential to overcome geographical barriers, thus contributing to a democratic access to health. New formats of interaction between health providers and health users are necessary in telehealth. Targeting adequate implementation, listening to actors involved with telehealth is of great importance. Objectives: To gather and analyze perceptions from population, health providers, patients, and users from a secondary level of care (Brazilian Unified Health System) towards health-related information online and telehealth. Methods: This project deepens into digital health literacy, telehealth, and implementation based on the following studies: I) Systematic review of qualitative studies: understand enablers and barriers to participate in telehealth and conduct a meta-synthesis; II) Observational study: to assess health providers, population and patients’ acceptability to telehealth using an e-survey; III) Qualitative study 1: to understand population perspectives towards telehealth using a thematic content analysis; IV) Qualitative study 2: use of critical theory to analyze how health system users interact with health-related information online. Results: Health providers, patients and population appear to have divided perceptions towards telehealth. Telehealth is identified as a mode for delivering educational content, self-management strategies, and advice on performance of therapeutic exercises. The digital environment of telehealth, focusing on health-related information online, can impact the relationship between health provider and patients, stressing ancient power relations and hierarchy mediated by knowledge and formal education. Enablers for participating in telehealth include flexibility and convenience of interventions. Barriers include impersonality, technology challenges, irrelevant content in relation to patients’ expectations, and low digital health literacy. Discussão: Giving voice to the actors participating in telehealth is one of multiple ways of analyzing its state of art. The internet as a resource and also environment used by telehealth imposes can strengthen power relation between health providers and patients. Our data can be added to the body of evidence in telehealth and further guide decision-making processes for the implementation of telehealth within public and private health domains. Conclusion: Several actors participate in telehealth and getting to know their demands and points of views can contribute to the telehealth potential of a broadened access to health.